Increasing Employees Performance through Motivation, Discipline, Work Environment, and Commitment: An Empirical Study on SMEs Employees - Siti Abadiyah; Hatoli Waruwu; Muhammad Johan; Multi Nadeak; Albertus M. Setyastanto (Universitas Pahlawan Tuanku Tambusai, 2023)
Empowerment of human resources is a non-stop process, but it is also the most important, especially about the performance of MSMEs in developing countries like Indonesia. The purpose of this study was to determine the effect of motivation, work discipline, work environment, and organizational commitment on the performance of MSME employees in Tangerang. The sample for this research was taken from 205 MSME employee respondents in Tangerang using a quantitative research method with a simple random sampling technique and using SEM (Structural Equation Model) and SmartPLS version 3.0 software as statistical tools. The results of this study indicate that motivation, work discipline, work environment, and organizational commitment have a positive and significant effect on the performance of MSME employees. The managerial implications of these findings suggest MSME management continues to pay attention to intangible factors as predictors of employee performance. The economic and social implications are discussed in more detail in this study report.